Serum uric acid was non-linearly associated with the risk of all-cause and cardiovascular death in individuals with coronary heart disease: a large prospective cohort study - Yan, Xuejiao; Gong, Jing; Wang, Zhenwei; Wu, Qiyong; Qi, Chunjian; Wang, Fangfang (Frontiers in Endocrinology, 2023)
Objective: To investigate the association of serum uric acid (SUA) with all-cause and cardiovascular death in individuals with coronary heart disease (CHD).Examination Survey (1999Survey ( -2015) ) were included in the analysis. Multivariate COX regression analysis, restricted cubic spline plot (RCS) and threshold effect were used to investigate the association between SUA and all-cause and cardiovascular death in individuals with CHD.In the fully adjusted model, when SUA was regarded as a continuous variable, it was closely associated with the risk of all-cause and cardiovascular death (P < 0.01). When all participants were divided into four groups according to the quartile of SUA, compared with Q1 group, only individuals in Q4 group had higher risk of all-cause and cardiovascular death (P = 0.002 and 0.034). The following subgroup analysis showed that the association between SUA and all-cause death risk was still statistically significant in individuals over 60 years old, male, with hypertension, without diabetes and with chronic kidney disease, while the association with cardiovascular death risk only persisted in individuals over 60 years old and male (P < 0.05). Further sensitivity analysis showed that SUA was still closely associated with all-cause and cardiovascular death, whether as a continuous variable or a classified variable (P = 0.007 and 0.044). RCS analysis revealed that SUA had a nonlinear association with all-cause and cardiovascular death risk (P for nonlinearity < 0.01). Threshold effect analysis showed that SUA below 345 umol/L was negatively associated with all-cause and cardiovascular death risk (P < 0.05), while SUA above 345 umol/L was positively associated with all-cause and cardiovascular death risk (P < 0.001), and the 2-piecewise regression model was better than the 1-line regression model (P for likelihood ratio test < 0.05).Conclusions: SUA had a nonlinear association with all-cause and cardiovascular death risk in individuals with CHD.